Performance trade-offs define a fundamental dental dichotomy in mammals - Narimane Chatar; Melvin Vankelst; Alejandro Pérez-Ramos; Tahlia I. Pollock; Davide Tamagnini; Margot Michaud; Levi Yoder Raskin; Z. Jack Tseng (Science, 2026)
Teeth define mammalian evolution, and one of many adaptive dental breakthroughs in crown mammals is the tribosphenic molar: a tooth with a dual shearing-crushing function, often considered a key adaptation in crown mammals. However, we do not know how potential trade-offs between these antagonistic functions may influence the macroevolutionary outcomes of mammalian lineages. Here, we show that predatory mammals evolved dichotomized performance in their tribosphenic carnassial teeth, with slicing constrained to a narrow set of optimal phenotypes and crushing exhibiting redundant solutions. Less than 1% of predators evolved optimized shearing and crushing. The fundamental trade-off in functions of the tribosphenic architecture promoted divergent macroevolutionary specializations rather than functional duality. These results highlight how key innovations can drive early evolutionary success while simultaneously constraining subsequent diversification.